Effects of cooler shape and position on solidification of phase change material in a cavity - Öztop, Hakan Fehmi; Kiyak, Burak; Biswas, Nirmalendu; Selimefendigil, Fatih; Cosanay, Hakan (Elsevier, 2024)
Background: For balancing the imbalance between the energy supply and demand, phase-change materials (PCMs) provide an efficient means in terms of thermal energy storage and release. The performance of the energy storage is primarily dependent on the melting as well as the solidification process of the storage medium. Faster charging or discharging of the thermal energy is a primary concern for any thermal energy storage unit. On this background, the present study explores the novel approach for enhancing the solidification process of PCM considering the effects of cooler shape (namely semi-circular, triangular, and rectangular) and their position (namely top, side, and bottom) in a molten PCM-filled enclosure. The middle portion of the cooler wall is curved; whereas the remaining cooler wall is straight maintaining the same cooler wall length. Methods: To analyze the solidification process, the involved transport equations are solved numerically following a finite volume-based computational approach using Ansys Fluent solver in conjunction with the appropriate boundary conditions. The computational model is generated for all the geometry comprising different shapes, as well as positions of the cooler wall. The third-order upwind scheme (QUICK) technique is utilized to discretize the momentum and energy equations. This scheme is well capable to accurately capture the gradients in the temperature and flow domains. Furthermore, the semi-implicit pressure-linked equation (SIMPLE) technique is utilised to address the pressure-velocity coupling. The resolved data are then saved as selective variables (U, V, and theta), which undergo post-processing to produce a local thermo-fluid flow field and extract average data. Significant findings: The shape, as well as the position of a cooler, dictates the solidification process in an energy storage system. Thermal energy storage with a triangular-shaped cold wall positioned at the top could be opted as an appropriate design approach of an efficient energy storage system compared to a semi-circular or rectangular-shaped cooler model. The shortest solidification time of PCM occurs when the cooler wall is positioned at the top. The top position of the cooler having a triangular shape with higher Grashof number (Gr) values leads to a faster solidification process. Some ideas for possible future research areas in this field are provided after a comprehensive examination.
Keywords: Solidification; Phase change material (PCM); Cooler shape and position; Energy storage; Heat transfer